Level of understanding of Alzheimer disease among caregivers and the general population - Jorge, C; Cetó, M; Arias, A; Blasco, E; Gil, M P; López, R; Dakterzada, F; Purroy, F; Piñol-Ripoll, G (Neurologia (Barcelona, Spain), 2021)
Understanding of Alzheimer disease is fundamental for early diagnosis and to reduce caregiver burden. The objective of this study is to evaluate the degree of understanding of Alzheimer disease among informal caregivers and different segments of the general population through the Alzheimer's Disease Knowledge Scale. We assessed the knowledge of caregivers in different follow-up periods (less than one year, between 1 and 5 years, and over 5 years since diagnosis) and individuals from the general population. Alzheimer's Disease Knowledge Scale scores were grouped into different items: life impact, risk factors, symptoms, diagnosis, treatment, disease progression, and caregiving. A total of 419 people (215 caregivers and 204 individuals from the general population) were included in the study. No significant differences were found between groups for overall Alzheimer's Disease Knowledge Scale score (19.1 vs. 18.8, P = .9). There is a scarce knowledge of disease risk factors (49.3%) or the care needed (51.2%), while symptoms (78.6%) and course of the disease (77.2%) were the best understood aspects. Older caregiver age was correlated with worse Alzheimer's Disease Knowledge Scale scores overall and for life impact, symptoms, treatment, and disease progression (P < .05). Time since diagnosis improved caregivers' knowledge of Alzheimer disease symptoms (P = .00) and diagnosis (P = .05). Assessing the degree of understanding of Alzheimer disease is essential to the development of health education strategies both in the general population and among caregivers.